2014
DOI: 10.5539/ijbm.v9n9p75
|View full text |Cite
|
Sign up to set email alerts
|

A Dimensional Analysis of the Relationship between Communication Satisfaction and Turnover Intention: The Mediating Role of Organizational Commitment

Abstract: By taking into consideration the significant increase in turnover rate in the recent years, we aimed to expand our understanding of the factors influencing employees' decision to leave the organization and consequently to provide managers and Human Resource Development (HRD) practitioners with more information to better manage employees' undesirable turnover. Thus, the relationship between the theoretically related communication satisfaction's dimensions and turnover intention was analyzed. A sample of 181 emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The findings of this study show similarities with the findings of other studies. One such study discovered that personal feedback, supervisory communication, and the communication climate dimensions of communication satisfaction are key factors in the intention to quit (Mustamil, Yazdi, Syeh, & Ali, ). Personnel with high levels of communication satisfaction negatively affect the intention to quit (Tsai, Chuang, & Hsieh, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study show similarities with the findings of other studies. One such study discovered that personal feedback, supervisory communication, and the communication climate dimensions of communication satisfaction are key factors in the intention to quit (Mustamil, Yazdi, Syeh, & Ali, ). Personnel with high levels of communication satisfaction negatively affect the intention to quit (Tsai, Chuang, & Hsieh, ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of immigrant nurses has determined that a supportive work environment decreases the intention to quit (Goh & Lopez, 2016). (Mustamil, Yazdi, Syeh, & Ali, 2014). Personnel with high levels of communication satisfaction negatively affect the intention to quit (Tsai, Chuang, & Hsieh, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies conducted in the West show contradictory evidence reporting that compensation has no significant impact on OC (Bhagat & Chassie, 1981;Malhorta, Budhwar, & Prowse, 2007;Shore & Barksdale, 1998). In Malaysian settings, some studies found that financial compensation and OC were positively correlated (Ibrahim & Boerhaneoddin, 2010;Kee, Ahmad, & Abdullah, 2016;Normala, 2010;Queiri & Dwaikat, 2016). This leads us to the following hypothesis:…”
Section: Satisfaction With Personnel Evaluationmentioning
confidence: 98%
“…On the other hand, recent work conducted in Malaysia finds a strong relationship between supervisor support and OC (Aghashahi, Davarpanah, Omar, & Sarli, 2013;Goh & Low, 2013;Lo & Min, 2009;Marmaya, Hitam, Torsiman, & Balakrishnan, 2011;Mustamil, Yazdi, Syeh, & Ali, 2014;Normala, 2010;Ramli & Desa, 2013). This may result from the fact that supervisors have a greater influence on the work activities of their subordinates in Malaysian organizations than is the case in the West, due to its collectivistic and hierarchical culture (Hofstede, 1980).…”
Section: Supervisor Supportmentioning
confidence: 99%
See 1 more Smart Citation